Method for producing carbon dioxide reducing photocatalyst particles
Ultrasonic treatment of a reaction solution with gallium oxide and a silver source supports silver nanoparticles on photocatalyst particles, addressing the challenge of dispersion and loading, resulting in improved CO selectivity and catalytic performance.
Patent Information
- Application Number
- JP2020174223
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-28
- Filing Date
- 2020-10-15
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2040-10-15
AI Technical Summary
Existing methods for producing carbon dioxide-reducing photocatalyst particles face challenges in supporting silver nanoparticles in a highly dispersed and high loading rate, leading to issues such as particle aggregation and reduced catalytic performance, particularly in terms of CO selectivity.
A method involving the use of ultrasonic treatment to reduce silver nanoparticles on gallium oxide particles, which includes preparing a reaction solution with gallium oxide and a silver source, irradiating it with ultrasonic waves to support metal silver nanoparticles, and optionally heat-treating the product to enhance dispersion and loading.
The method enables the production of photocatalyst particles with highly dispersed and supported silver nanoparticles, improving CO selectivity and catalytic performance by promoting charge separation and reaction intermediate generation, thereby enhancing CO gas generation.
Smart Images

Figure 0007619558000013 
Figure 0007619558000014 
Figure 0007619558000015
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing carbon dioxide reducing photocatalyst particles. [Background technology]
[0002] Water splitting and carbon dioxide reduction technology using semiconductor photocatalyst particles has attracted attention as a technology that can solve energy and environmental problems. By supporting nanoparticles made of silver (Ag) or the like as co-catalysts on these photocatalyst particles, it is expected that the effect of trapping electrons generated by photoexcitation and promoting charge separation and the effect of selecting carbon dioxide reduction products can be achieved. For example, with a normal photocatalyst, water is split into hydrogen (H2) and oxygen (O2) when irradiated with light. In contrast, with a photocatalyst supporting silver particles, carbon monoxide (CO) is generated together with hydrogen (H2) through the reduction of carbon dioxide (CO2). Gallium oxide particles supporting silver nanoparticles as co-catalysts (gallium oxide particles supporting silver nanoparticles) are known as such carbon dioxide reduction photocatalysts.
[0003] Carbon monoxide (CO) is an important starting material in the chemical and industrial industries, and can be reacted with hydrogen to synthesize various fuels and chemicals. Therefore, in a carbon dioxide reduction photocatalyst, it is desirable to have a high carbon monoxide production rate, i.e., a high CO selectivity. Here, CO selectivity is the ratio of the carbon monoxide (CO) gas generation rate to the total of the hydrogen (H2) gas generation rate (amount) and the carbon monoxide (CO) gas generation rate generated by the reduction reaction, as expressed in the following formula (1).
[0004]
number
[0005] As a method for supporting metal nanoparticles, there are conventionally known methods such as impregnation and photoelectrodeposition. For example, Patent Document 1 describes a method for reducing carbon dioxide, which includes irradiating light to CO2, H2O, and a photocatalyst to generate CO by a reaction that reduces CO2, using a catalyst in which silver is supported on gallium oxide by photoelectrodeposition or impregnation, adding gallium oxide powder to an alcoholic aqueous solution containing a silver precursor such as silver nitrate and mixing it, and then irradiating light to reduce the silver precursor, and impregnation adding gallium oxide to an aqueous solution of a silver precursor and stirring it, removing water, drying it by heating, and then calcining it in air (claims 1, 2, and
[0015] of Patent Document 1).
[0006] Furthermore, although not related to carbon dioxide reduction catalysts, Patent Document 2 discloses a method for producing a precious metal nanomaterial, which comprises the steps of irradiating ultrasonic waves to disperse one or more types of precious metal oxide in a solvent to obtain a precious metal oxide dispersion, and heating the precious metal oxide dispersion. It describes how the solvent further contains a carrier for supporting the precious metal, and how it is possible to obtain a precious metal nanomaterial supported with a high degree of dispersibility on the surface of the carrier, which can be suitably used as a catalyst for fuel cells, a catalyst for material synthesis, etc. (Claims 1, 6, and
[0014] of Patent Document 2). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2012-192302 A [Patent Document 2] JP 2008-24968 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, the inventors have found that the photocatalysts prepared by the impregnation method and photoelectrodeposition method proposed in Patent Document 1 have a certain effect but have room for improvement. That is, in order to fully exert the effect of the co-catalyst silver (Ag), it is desirable to increase the amount of silver supported to a certain extent. In addition, it is desirable for the particle size of silver to be small, on the order of several tens of nm. This is because catalytic activity is lost if the particle size is too large. However, with photocatalyst particles prepared by the impregnation method and photoelectrodeposition method, there is a problem that the silver particles aggregate and the particle size becomes large when the silver concentration (supported amount) is increased. Therefore, it is difficult to support a large amount of silver nanoparticles with a small particle size.
[0009] Patent Document 2 does not intend to use precious metal nanomaterials as carbon dioxide reduction photocatalysts, much less to reduce the particle size of nanomaterials to the order of several tens of nm. In fact, in the examples of Patent Document 2, it merely teaches that precious metal (Pt) nanoparticle-supported spherical carbon and precious metal (Pt) nanotubes are prepared, and that they are suitable for use as catalysts for fuel cells, catalysts for material synthesis, medical and food additives, and conductive pastes (
[0043] to
[0062] of Patent Document 2).
[0010] When synthesizing metal nanoparticles, a method is known in which uniform and fine particles are synthesized by lowering the raw material concentration and using a large amount of organic protective agent. However, when photocatalyst particles are produced using this method, there are problems in that the yield of photocatalyst particles is low and the organic protective agent adheres to the particle surface. Since the attached organic protective agent reduces the catalytic activity, the catalyst particles must be calcined at high temperatures to decompose and remove it. In catalyst particles that have been calcined in this way, the particle size of the metal nanoparticles becomes large. Therefore, it is difficult to highly disperse and support fine silver nanoparticles in a large amount using conventional methods, and there are limitations in efficiently producing photocatalyst particles with excellent catalytic performance, especially CO selectivity.
[0011] The present inventors have conducted studies in consideration of such conventional problems, and have discovered that a simple method of irradiating gallium oxide particles and a silver supply source with ultrasonic waves can precipitate silver nanoparticles as a promoter with high dispersion and high loading, thereby making it possible to obtain a photocatalyst with improved CO selectivity.
[0012] The present invention was completed based on such findings, and an object of the present invention is to provide a method for producing carbon dioxide reduction photocatalyst particles that can precipitate silver nanoparticles with high dispersion and high loading rate. [Means for solving the problem]
[0013] The present invention encompasses the following embodiments. In this specification, the expression "to" includes both ends of the expression. In other words, "X to Y" is synonymous with "X or more and Y or less."
[0014] Providing gallium oxide (Ga2O3) particles and a silver (Ag) source; adding the gallium oxide particles and the silver source to a reduction solution to prepare a reaction solution; and A method for producing carbon dioxide reducing photocatalyst particles, comprising: a step of irradiating the reaction solution with ultrasonic waves to produce gallium oxide particles carrying metallic silver nanoparticles. Effect of the Invention
[0015] According to the present invention, there is provided a method for producing carbon dioxide reducing photocatalyst particles that can precipitate silver nanoparticles with high dispersion and high loading rate. [Brief description of the drawings]
[0016] [Figure 1] 1 shows the mechanism of silver nanoparticle loading. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of an evaluation device. [Diagram 3] The mechanism of photocatalytic reaction is shown. [Figure 4] 1 shows an optical photograph of an example sample. [Diagram 5]1 shows XRD patterns of the example and comparative sample. [Figure 6] 1 shows XRD patterns (enlarged views) of samples of the example and comparative example. [Figure 7] 1 shows XRD patterns (enlarged views) of samples of the example and comparative example. [Figure 8] 1 shows an SEM photograph of an example sample (Example 3). [Figure 9] 1 shows an SEM photograph of a comparative sample (Comparative Example 2). [Figure 10] 1 shows a STEM photograph of an example sample (Example 3). [Figure 11] 1 shows a STEM photograph of an example sample (Example 4). [Figure 12] 1 shows a STEM photograph of a comparative sample (Comparative Example 1). [Figure 13] 1 shows a STEM photograph of a comparative sample (Comparative Example 2). [Figure 14] 1 shows the particle size distribution of silver nanoparticles in example samples. [Figure 15] 1 shows the particle size distribution of silver nanoparticles in the samples of the examples and comparative examples. [Figure 16] 1 shows the diffuse reflectance spectra of the example and comparative example samples. [Figure 17] The relationship between the amount of silver loaded and the CO selectivity is shown. [Figure 18] 4 shows SEM photographs of the example sample before and after heat treatment. [Figure 19] TG curves of the example sample before and after heat treatment are shown. [Figure 20] 4 shows DTA curves of the example sample before and after heat treatment. [Figure 21] 4 shows XRD patterns of the example sample before and after heat treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] A specific embodiment of the present invention (hereinafter, referred to as the present embodiment) will be described below. However, the present invention is not limited to the following embodiment, and various modifications are possible within the scope of the present invention.
[0018] 1. Photocatalyst particle manufacturing method The method for producing carbon dioxide reduction photocatalyst particles (hereinafter sometimes collectively referred to as "photocatalyst particles") of this embodiment includes the following steps: a step of preparing gallium oxide (Ga2O3) particles and a silver (Ag) supply source (preparation step), a step of adding the gallium oxide particles and the silver supply source to a reduction solution to prepare a reaction solution (mixing step), and a step of irradiating the reaction solution with ultrasonic waves to prepare gallium oxide particles carrying metallic silver nanoparticles (ultrasonic treatment step). Details of each step are described below.
[0019] <Preparation process> In the preparation step, gallium oxide (Ga2O3) particles and a silver (Ag) supply source are prepared. The gallium oxide (Ga2O3) particles are not particularly limited as long as they are used in photocatalysis. Ga2O3 is known to be of α-type, β-type, γ-type, δ-type, and ε-type, and any of them may be used. However, β-type (β-Ga2O3), which is a stable oxide, is preferable. The size of the particles is also not particularly limited. For example, the average particle diameter of the particles is 0.3 to 5.0 μm. Furthermore, the shape of the particles is also not particularly limited. For example, spherical, irregular, and anisotropic shapes (rod or plate-like, etc.) can be mentioned. When the particles are rod-like, for example, those with a major axis diameter of 1.0 to 5.0 μm and a minor axis diameter of 0.3 to 1.0 μm can be used.
[0020] The silver (Ag) supply source is not limited as long as it can supply silver. Specific examples include oxides, inorganic metal salts, and / or organic metal compounds. Examples of inorganic metal salts include nitrates, chlorides, and / or sulfates. The silver supply source may be soluble in the reducing solution, or may not be soluble in the reducing solution. Preferably, the silver supply source includes silver oxide. Since silver oxide is composed only of silver ions and oxygen ions, it is easy to handle and there is no problem with waste disposal. As silver oxide, Ag2O, AgO, and Ag2O3, which have different oxidation numbers of silver, are known, and any of them can be used. However, Ag2O, which is more easily available, is preferred. The size of the silver supply source is also not particularly limited. For example, the average particle size of the silver supply source is 0.3 to 3.0 μm.
[0021] <Mixing process> In the mixing step, the prepared gallium oxide particles and silver source are added to the reduction solution to prepare a reaction solution. The mixing ratio of the gallium oxide particles and the silver source can be adjusted so that the amount of silver carried in the final photocatalyst is the desired value. If the amount of silver carried is too small, it becomes difficult to fully utilize the effect of the co-catalyst. As a result, the CO gas generation rate and CO selectivity are low when the photocatalyst is used for CO2 reduction. On the other hand, if the amount of silver carried is too high, the CO gas generation rate decreases.
[0022] The reducing liquid is not limited as long as it is a liquid having reducing properties. It may be a liquid having reducing properties by itself, or may be a liquid having no reducing properties in which a reducing agent is dissolved. However, a liquid having reducing properties by itself is preferable. It may not contain a separate reducing agent. As such a reducing liquid, alcohols such as ethanol and propanol, which are less toxic and easily available, are preferable. A mixed liquid of alcohols and water can also be used. However, when using a mixed liquid, if the water content is excessively high, it becomes difficult to exert a sufficient reducing effect. Therefore, the water content in the reducing liquid is preferably 50% by volume or less, more preferably 25% by volume or less. The lower limit of the water content is not particularly limited, and may be 0% by volume.
[0023] <Ultrasonic treatment process> In the ultrasonic treatment step, the reaction solution is irradiated with ultrasonic waves to produce gallium oxide particles carrying metallic silver nanoparticles. During this process, the surface of the silver source in the reaction solution is ultrasonically reduced to become metallic silver (Ag) nanoparticles, which are then carried on the surface of the gallium oxide particles. The gallium oxide particles carrying metallic silver nanoparticles become photocatalyst particles.
[0024] The mechanism of metallic silver nanoparticle support is explained using Figure 1. When ultrasonic waves are irradiated, compression waves are generated in the reaction solution, which generates repeated positive and negative pressures. During negative pressure cycles, countless fine bubbles are generated in the reaction solution due to evaporation. During positive pressure cycles, these bubbles collapse and give a strong impact force to the surroundings. This phenomenon is called ultrasonic cavitation. Cavitation uniformly disperses the gallium oxide particles and silver source in the reaction solution, and cleans the surface. Cavitation also generates tiny hot spots of high temperature and pressure. The generated hot spots decompose and reduce the silver source, and also act on the reaction solution to generate radicals, which promote the decomposition and reduction of the silver source. In this way, metallic silver nanoparticles are generated from the silver source.
[0025] For example, when solid silver oxide (Ag2O) is used as the silver supply source, hot spots and radicals act on the silver oxide, and the silver oxide is decomposed and reduced on the surface, resulting in the precipitation of silver nanoparticles. The silver nanoparticles grow gradually, and when they grow to a certain extent, the interfacial stress between the silver oxide and the silver nanoparticles becomes a limit and they are detached. Alternatively, an intermediate product is generated from the silver oxide by the action of ultrasound, and hot spots and radicals act on this intermediate product to generate silver nanoparticles in the reaction solution. The detached or generated silver nanoparticles move to the surface of the gallium oxide particles by the physical action of ultrasound and are adsorbed there. In this way, gallium oxide particles carrying silver nanoparticles are obtained. The silver nanoparticles generated by ultrasonic reduction are minute. In addition, since no organic protective agent or high-temperature firing is required, it is possible to produce gallium oxide particles (photocatalyst particles) carrying silver nanoparticles in a fine state.
[0026] If the photocatalyst particles contain a silver source other than silver nanoparticles, it may be difficult to fully exert the effect of the co-catalyst. According to the ultrasonic treatment of this embodiment, it is possible to obtain photocatalyst particles that contain almost no silver source (silver oxide, etc.). For example, it is possible to obtain photocatalyst particles in which no peak of silver oxide (Ag2O) is observed in the X-ray diffraction pattern.
[0027] There is no need to use a special device for the ultrasonic treatment, and a device equipped with a normal ultrasonic oscillation source may be used. For example, a commercially available ultrasonic cleaner may be used. The treatment may be performed under normal conditions. For example, the frequency of the ultrasonic waves may be 20 to 100 kHz, or 28 to 45 kHz. The ultrasonic treatment may be performed continuously at the same frequency, or the frequency may be switched during the treatment using a frequency oscillation switching mode. The frequency may be switched once or multiple times. By performing the treatment in a frequency oscillation switching mode (for example, a two-frequency switching oscillation mode of 28 kHz / 45 kHz), it is possible to further improve the dispersibility of the gallium oxide particles in the liquid. In addition, the output of the ultrasonic waves may be 10 to 500 W, or 50 to 200 W. Furthermore, the treatment time may be 1 to 10 hours. By extending the treatment time, it is possible to convert all of the silver source into silver nanoparticles and support them on the gallium oxide particles. On the other hand, by shortening the treatment time, it is possible to adjust the amount of silver nanoparticles supported.
[0028] The product obtained by ultrasonic treatment (gallium oxide particles carrying metallic silver nanoparticles) exists in a dispersed or precipitated state in the reaction solution. Therefore, the product is recovered from the reaction solution and dried. For recovery, known separation means such as filtration or centrifugation may be used. Drying may be performed under conditions that do not cause excessive particle growth of the silver nanoparticles, for example, at 100°C or less.
[0029] <Heat treatment process> If necessary, the gallium oxide particles carrying metallic silver nanoparticles may be heat-treated at a temperature of 100°C or higher in an oxygen-containing atmosphere. Heat treatment of the silver-loaded gallium oxide particles produced by the ultrasonic loading method can remove the organic matter derived from ethanol remaining on the particle surface and further reduce the particle size of the silver (Ag) nanoparticles. This heat treatment allows the selective generation of CO when used as a CO2 reduction photocatalyst.
[0030] The heat treatment is preferably carried out at 100°C or higher in an oxygen-containing atmosphere. There is no need to use special equipment for the heat treatment, and a general electric furnace capable of firing in air can be used. In addition, at temperatures below 100°C, the effect on the decomposition of organic matter and the particle size of silver (Ag) nanoparticles is small, so the effect cannot be expected.
[0031] In this manner, photocatalyst particles consisting of metal nanoparticle-supported gallium oxide particles can be obtained.
[0032] In the manufacturing method of this embodiment, the average particle diameter of the metallic silver nanoparticles is preferably 10.0 to 50.0 nm. Silver nanoparticles having an average particle diameter of 10.0 nm or more can be obtained without the need to lower the Ag concentration (loading amount) or add an organic surface protective agent. On the other hand, by making the average particle diameter 50.0 nm or less, it is possible to prevent problems such as loss of function as a cocatalyst, such as catalytic activity, and reduction in the surface active sites of gallium oxide particles. The average particle diameter is more preferably 10.0 to 30.0 nm. The average particle diameter can be obtained by observing the photocatalyst particles using a transmission electron microscope (TEM). As an example, a method of determining the particle diameter distribution of silver nanoparticles by visual observation or image analysis software and calculating the average value from this particle diameter distribution can be mentioned.
[0033] In the manufacturing method of this embodiment, the amount of metallic silver nanoparticles supported is preferably 0.3 to 10.0% by mass relative to the gallium oxide particles. As described above, if the amount supported is too small, the CO gas generation rate and CO selectivity will be low. On the other hand, if the amount supported is too large, the CO gas generation rate will decrease. The amount supported can be adjusted by controlling the blending amount of the silver source and the ultrasonic treatment conditions. The amount of silver nanoparticles supported may be 0.5% by mass or more, 1.0% by mass or more, 3.0% by mass or more, or 5.0% by mass or more. The amount supported may be 7.5% by mass or less, 5.0% by mass or less, 3.0% by mass or less, or 1.0% by mass or less.
[0034] In the manufacturing method of this embodiment, the CO selectivity of the photocatalyst particles is preferably 30% or more in a CO2 reduction photocatalyst performance evaluation test. This makes it possible to increase the proportion of the amount of CO gas generated by CO2 reduction. The CO selectivity may be 40% or more, 50% or more, 60% or more, or 70% or more. The upper limit of the CO selectivity is not particularly limited, but is typically 90% or less, more typically 80% or less.
[0035] The CO2 reduction photocatalytic performance evaluation test may be performed using a known evaluation device. An example of the evaluation device is shown in FIG. 2. The evaluation device (2) is composed of a tank (4) and a high-pressure mercury (Hg) lamp (6) installed inside the tank (4). The tank (4) is filled with an evaluation solution (22). The tank (4) is also equipped with a gas inlet pipe (8), a gas outlet pipe (10), a pH meter (12), a rubber stopper (14), and a stirrer (16). A bubbling filter (18) is installed at the tip of the gas inlet pipe (8). The mercury lamp (6) is cooled by cooling water (20) flowing around it.
[0036] The evaluation test may be performed as follows. Pure water, sodium bicarbonate (NaHCO3), and a sample (photocatalyst particles) are mixed to prepare an evaluation solution (22). This evaluation solution (22) is placed in a tank (4) of an evaluation device (2) and stirred with a stirrer (16). Carbon dioxide (CO2) gas (30) is blown in through a gas inlet pipe (8), and at the same time, UV light from a high-pressure mercury lamp (6) is irradiated onto the evaluation solution (22). After irradiation for a predetermined time, the generated gas (32) is introduced through a gas outlet pipe (10) into a gas chromatograph (34) and analyzed there. The generation rates (amounts) of hydrogen (H2), oxygen (O2), and carbon monoxide (CO) are determined by this analysis. The obtained generation rates are used to calculate the CO selectivity based on the following formula (1).
[0037]
number
[0038] The mechanism of CO2 reduction by gallium oxide particles carrying metallic silver nanoparticles (photocatalyst particles) is explained with reference to Figure 3. When light with energy hν is irradiated onto the particles, electrons (e - ) and holes (h + In this process, the metallic silver nanoparticles (promoter) separate charges (electrons e - and hole h + The separation of holes (h + ) reacts with the surrounding water (HO), and the reaction shown in the following formula (2) proceeds to the right, producing oxygen (O2) and protons (H + ) and electrons (e - ) is converted into carbon dioxide (CO2) and protons (H + ), the reactions shown in the following formulas (3) and (4) proceed to the right, producing carbon monoxide (CO), water (H2O), and hydrogen (H2). In principle, the reactions shown in the following formula (5) proceed when the reactions in the following formulas (2) to (4) are combined.
[0039]
number
number
number
number
[0040] When the reactions of the above formulas (3) and (4) occur to the same extent, the CO selectivity (CO generation rate / (H2 generation rate+CO generation rate)) is constant as shown in the above formula (5). However, in reality, these reactions do not necessarily occur to the same extent. When the reaction of the above formula (3) occurs preferentially, the CO selectivity increases.
[0041] In this regard, it has been reported that in the reaction of formula (3) above, carbon dioxide (CO2) is adsorbed on the catalyst surface as carbonate species, and when irradiated with light, it changes to a formate species, which is a reaction intermediate, and then interacts with water molecules to become carbon monoxide (CO). This report also suggests that the silver promoter promotes the generation of reaction intermediates. Therefore, by enhancing the effect of charge separation and the effect of generating reaction intermediates by metallic silver nanoparticles (promoter), it is expected that the reaction of formula (3) above will occur preferentially, and the CO selectivity will be further improved.
[0042] In the manufacturing method of this embodiment, it is preferable that the photocatalyst particles have a peak in the wavelength range of 350 to 550 nm in the diffuse reflectance spectrum. This can further improve the catalytic performance of the photocatalyst particles. The diffuse reflectance spectrum is an absorption spectrum obtained by a diffuse reflectance method. When light is irradiated onto a solid sample such as a powder, a part of the light goes out of the sample through a scattering process. In the scattering process, a part of the irradiated light is reflected by the surface of the sample, and the rest penetrates into the sample. A part of the incident light that penetrates is absorbed by the electronic transition state of the sample, and the rest goes out of the sample. The absorption spectrum can be obtained from the incident light intensity of ultraviolet light or visible light and the light intensity after the scattering process.
[0043] The reason why the catalytic performance is improved by having a peak in a specific wavelength range (350-550 nm) is unclear. However, it is speculated that the particle size of the metallic silver nanoparticles and the electronic transition state are related. In other words, the spectrum obtained by the diffuse reflectance method (diffuse reflectance spectrum) reflects the electronic transition state of the sample, such as the valence of the species, the coordination structure, and the ligand field. In addition, when the sample is a fine particle, it may show different absorption energy depending on the particle size. For example, it is known that when the metallic silver particles are fine particles, they give an absorption band in the wavelength range corresponding to plasmon resonance. In this respect, the metallic silver nanoparticles (co-catalyst) generated by ultrasonic reduction treatment have a small particle size. It is also considered that the high temperature and high pressure hot spots and the action of radicals generated during ultrasonic treatment are in a unique electronic transition state. In fact, it has been reported that the hot spots generated by ultrasonic waves are as high as nearly 5000°C, and it is easy to predict that the electronic transition state will change if such a high temperature hot spot acts even for an instant. It is speculated that the absorption of light in a specific wavelength range occurs due to the combined action of this fine particle size and the unique electronic transition state.
[0044] According to the manufacturing method of this embodiment, it is possible to deposit metallic silver nanoparticles with high dispersion and high loading rate. In fact, it has been confirmed that silver nanoparticles can be loaded at a high concentration of 5 mass %, thereby obtaining photocatalyst particles with excellent CO selectivity. In contrast, it is difficult to load metallic silver nanoparticles with high dispersion and high loading rate by the impregnation method and photoelectrodeposition method proposed in the past. For example, Patent Document 1 describes that the amount of silver loaded is 0.2 to 2 mass % with respect to gallium oxide in the case of photoelectrodeposition method and 0.05 to 2% in the case of impregnation method, and that if it is more than the optimal range, the particle diameter of the silver nanoparticles becomes large, the effect of catalytic activity, etc. is lost, or the surface active sites of gallium oxide are reduced (
[0014] and
[0015] of Patent Document 1).
[0045] Furthermore, in the manufacturing method proposed in Patent Document 2, ultrasonic treatment is performed only to disperse the precious metal oxide, and the precious metal oxide is reduced in a heating step after ultrasonic treatment (Patent Document 2,
[0038] ). Therefore, it is clearly different from the manufacturing method of the present embodiment, in which the silver source (silver oxide, etc.) is reduced by ultrasonic treatment. In the manufacturing method of the present embodiment, it is possible to support sufficiently reduced silver nanoparticles without heating after ultrasonic treatment.
[0046] The details of the mechanism by which the photocatalyst particles of this embodiment show high CO selectivity are unclear. However, it is speculated that the particle size of the metallic silver nanoparticles mentioned above and the electronic transition state may be related. In other words, the silver nanoparticles acting as co-catalysts separate charges (electrons e - and hole h + It also plays an important role in forming the reaction intermediates (formate species) that are generated when CO gas is produced. In this regard, the metallic silver nanoparticles generated by ultrasonic reduction are small in particle size and in a unique electronic transition state. It is speculated that these factors work together to enhance the effects of charge separation and reaction intermediate generation of metallic silver nanoparticles.
[0047] In addition, according to the manufacturing method of this embodiment, although not limited thereto, it is possible to use a compound such as silver oxide that is not dissolved in the reaction solution as a silver supply source in a solid state. When a compound that is not dissolved in the reaction solution is used, the reaction solution does not contain harmful substances such as anions, and waste liquid treatment is easy. In contrast, the impregnation method and photoelectrodeposition method proposed in Patent Document 1 use a precursor solution such as an aqueous solution in which silver nitrate is dissolved. Anions such as nitrate ions contained in such precursor solutions are harmful substances that cause air pollution. Therefore, the impregnation method and photoelectrodeposition method require waste liquid treatment to detoxify harmful substances. However, the manufacturing method of this embodiment does not exclude the use of a compound that dissolves in the reaction solution. Even in such a case, the effect of precipitating metallic silver nanoparticles with high dispersion and high loading rate can be obtained. EXAMPLES
[0048] The present embodiment will be described in more detail with reference to the following examples, but the present invention is not limited to the following examples.
[0049] [Experimental Example A] (1) Preparation of photocatalyst particles Example 1 Photocatalyst particles (metallic silver nanoparticle-supported gallium oxide particles) were produced by reducing silver nanoparticles using ultrasonic treatment. The silver concentration (supported amount) relative to gallium oxide was 0.5 mass%. Specifically, the sample was produced as follows.
[0050] <Preparation process> Gallium oxide particles (Ga2O3, Kojundo Chemical Laboratory Co., Ltd.) and silver oxide (Ag2O, Fujifilm Wako Pure Chemical Co., Ltd.) were prepared. The gallium oxide particles had a purity of 99.99% and the average particle diameter was approximately 3 μm in the long axis and approximately 1 μm in the short axis. The silver oxide particles had a purity of 99% and were aggregates with a primary particle diameter of approximately 2 μm.
[0051] <Mixing process> The prepared gallium oxide particles (1 g) and silver oxide (5 mg) were added to a reducing solution (50 mL). Ethanol (Fujifilm Wako Pure Chemical Industries, Ltd.) was used as the reducing solution. This produced a reaction solution.
[0052] <Ultrasonic treatment process> The resulting reaction solution was placed in an ultrasonic device (Honda Electronics Co., Ltd., WT-100-M) and subjected to ultrasonic treatment. The ultrasonic treatment was performed under the conditions of a two-frequency switching oscillation of 28 kHz and 45 kHz and an output of 100 W. The treatment time was changed between 0 and 3 hours. At this time, the temperature of the reaction solution was maintained at 40°C. By this treatment, silver oxide (Ag2O) in the reaction solution was reduced and changed to silver (Ag). Next, the product generated by the treatment was filtered, washed with ethanol (10 mL), and dried in air at 60°C for 0.5 hours to obtain gallium oxide particles carrying metallic silver nanoparticles as photocatalyst particles.
[0053] Example 2 Except for changing the amount of silver oxide added in the mixing step to 11 mg, photocatalyst particles were produced in the same manner as in Example 1. The silver concentration relative to gallium oxide was 1.0 mass %.
[0054] Example 3 Except for changing the amount of silver oxide added in the mixing step to 32 mg, photocatalyst particles were produced in the same manner as in Example 1. The silver concentration relative to gallium oxide was 3.0 mass %.
[0055] Example 4 Except for changing the amount of silver oxide added in the mixing step to 54 mg, photocatalyst particles were produced in the same manner as in Example 1. The silver concentration relative to gallium oxide was 5.0 mass %.
[0056] Example 5 Photocatalyst particles were prepared in the same manner as in Example 2, except that a mixed liquid consisting of ethanol (37.5 mL) and pure water (12.5 mL) was used as the reducing liquid.
[0057] Example 6 Photocatalyst particles were produced in the same manner as in Example 2, except that a mixed liquid consisting of ethanol (25.0 mL) and pure water (25.0 mL) was used as the reducing liquid.
[0058] Comparative Example 1 Photocatalyst particles were produced by reducing silver nanoparticles using the conventional impregnation method. First, ultrapure water (20 mL), gallium oxide (1 g), and an aqueous silver nitrate solution (0.1 M, 2.8 mL) were mixed, and the resulting mixed solution was heated at 80°C for 1 hour using a water bath. Next, the heated mixed solution was dried in air at 80°C for 3 hours, and the resulting dried product was baked at 450°C for 2 hours to obtain photocatalyst particles. The silver concentration relative to gallium oxide was 3.0 mass%.
[0059] Comparative Example 2 Silver nanoparticles were reductively generated by the conventional photoelectrolysis method (photoelectrodeposition method) to produce photocatalyst particles. First, ultrapure water (1 L), gallium oxide (1 g), and an aqueous silver nitrate solution (0.1 M, 2.8 mL) were mixed, and argon (Ar) gas was blown into the resulting mixed solution for gas replacement. Next, while blowing argon gas at a flow rate of 30 mL / min, UV light was irradiated with a 400 W high-pressure Hg lamp for 5 hours to reduce silver (Ag) ions. The solution after light irradiation was filtered, and the powder was recovered. The recovered powder was dried at room temperature to obtain photocatalyst particles. The silver concentration relative to gallium oxide was 3.0% by mass.
[0060] Comparative Example 3 Photocatalyst particles were prepared in the same manner as in Example 2, except that pure water (50 mL) was used instead of the reducing solution (ethanol) in the mixing step. However, even after performing ultrasonic treatment for 3 hours, no change was observed in the color of the particles. It is considered that the reducing power is low with only water, and the reduction reaction from silver oxide to silver does not proceed.
[0061] Comparative Example 4 Silver nanoparticles were not supported, and gallium oxide particles alone were used as photocatalyst particles.
[0062] (2) Evaluation of photocatalyst particles For the samples obtained in Examples 1 to 6, Comparative Examples 1, 2, and 4, evaluations of various properties were performed as follows. In Examples 1 to 6, evaluations other than visual observation were performed on the samples subjected to ultrasonic treatment for 3 hours. Also, since the reduction reaction from silver oxide to silver did not proceed in the sample of Comparative Example 3, no evaluation was performed.
[0063] <Visual observation> The samples were visually observed to examine their color tone.
[0064] <X-ray diffraction (XRD)> The samples were analyzed by X-ray diffraction to examine their crystal phases. The analysis conditions were as follows.
[0065] - X-ray diffractometer: Spectris Co., Ltd., X’Pert PRO MRD - X-ray source: CuKα ray - Tube voltage: 45 kV - Tube current: 40 mA - Scanning speed: 5.5° / min - Scanning range (2θ): 20 - 60°
[0066] <SEM Observation> The sample was observed using a scanning electron microscope (SEM; Carl ZEISS, ULTRA55). The observation was carried out under the condition of an acceleration voltage of 1 kV.
[0067] <STEM Observation> The sample was observed using a scanning transmission electron microscope (STEM; Hitachi High-Technologies Corporation, HD2700), and the average particle size of silver nanoparticles was determined. The observation was carried out under the condition of an acceleration voltage of 200 kV with a transmission electron image. Also, the average particle size was determined as follows. More than 70 particle sizes were measured from the STEM image, and the average value was taken as the average particle size.
[0068] <Diffuse Reflection Spectrum> The diffuse reflection spectrum of the sample in the solid state was measured in the wavelength range of 200 - 800 nm using an ultraviolet-visible spectrophotometer (JASCO Corporation, V-650).
[0069] <CO2 Reduction Photocatalytic Performance> The CO2 reduction photocatalytic performance of the sample was evaluated using the evaluation apparatus shown in Figure 2. First, ultrapure water (1 L), NaHCO3 (0.1 M), and photocatalyst particles (0.5 g) were mixed to prepare an evaluation solution. Next, this evaluation solution was placed in the tank of the evaluation apparatus, and while blowing carbon dioxide (CO2) gas at a flow rate of 30 mL / min, UV light was irradiated with a 400 W high-pressure Hg lamp. The gas generated after 1 hour of irradiation was analyzed using gas chromatography (Shimadzu Corporation, GC-8A) to determine the generation rates of H2, O2, and CO. Then, the CO selectivity was calculated based on the following formula (1).
[0070]
Equation
[0071] (3) Evaluation results <Visual observation> Figure 4 shows optical photographs of samples (Examples 1 to 4 and Comparative Example 4) prepared by changing the ultrasonic irradiation time and the silver loading amount. As the ultrasonic irradiation time increased, the color tone changed from white to brown. Also, the higher the silver loading amount, the darker the color tone became.
[0072] <X-ray diffraction (XRD)> The X-ray diffraction (XRD) patterns obtained for Examples 1 to 4 and Comparative Example 4 are shown in FIGS. 5 to 7 together with the patterns of silver (Ag) and silver oxide (Ag2O). Here, FIGS. 6 and 7 are enlarged views of FIG. 5. In the samples prepared by the ultrasonic reduction method (Examples 1 to 4), no pattern corresponding to silver oxide (Ag2O) was observed. In particular, as shown in the enlarged view of FIG. 6, even in the sample with a high silver loading amount of 5 mass% (Example 4), the peak peculiar to silver oxide (Ag2O) observed near 2θ = 32.7° was not observed. From this, it was found that Examples 1 to 4 do not contain silver oxide. On the other hand, in these samples (Examples 1 to 4), a pattern corresponding to silver (Ag) was observed. In particular, as shown in the enlarged view of FIG. 7, in the samples with a silver loading amount of 3 mass% or 5 mass% (Examples 3 and 4), a peak peculiar to silver (Ag) observed near 2θ = 44.5° was observed, and its intensity was higher as the loading amount was higher. From this, it was found that in the samples prepared by the ultrasonic reduction method, all of the silver source (silver oxide) as the raw material was reduced to silver.
[0073] <SEM observation> SEM photographs obtained for the samples of Example 3 and Comparative Example 2 are shown in FIGS. 8 and 9, respectively. The bright (white) particles present in the figures are silver nanoparticles. In any of the samples, silver nanoparticles were supported on the surface of gallium oxide particles. However, in the sample prepared by the ultrasonic reduction method (Example 3), the particle size of silver nanoparticles was small, while in the sample prepared by the photoelectrolysis method (Comparative Example 2), the particle size was large. Although not shown in the figures, in the samples prepared by the ultrasonic reduction method (Examples 1 to 6), silver nanoparticles were uniformly generated and almost no aggregated particles were observed. Also, when the loading amount was increased, although the number of silver nanoparticles increased, almost no change was observed in their particle size. Furthermore, the samples prepared using a mixed solution of ethanol and pure water as the reducing solution (Examples 5 and 6) had almost the same particle size and distribution state of silver nanoparticles as the sample prepared using ethanol alone (Example 2).
[0074] <STEM Observation> STEM photographs obtained for the samples of Example 3, Example 4, Comparative Example 1 and Comparative Example 2 are shown in FIGS. 10 to 13, respectively. The black particles present in the figures are silver nanoparticles. Similar to the results of the SEM photographs, in any of the samples, silver nanoparticles were supported on the surface of gallium oxide particles. Also, in the samples prepared by the ultrasonic reduction method (Example 3 and Example 4), the particle size of silver nanoparticles was small, while in the samples prepared by the impregnation method or the photoelectrolysis method (Comparative Example 1 and Comparative Example 2), the particle size was large.
[0075] The particle size distributions of silver nanoparticles determined based on the STEM photographs are shown in FIGS. 14 and 15. Also, the average particle sizes calculated from the particle size distributions are shown in Table 1. All of the samples prepared by the ultrasonic reduction method (Examples 1 to 4) had an average particle size within the range of 20.0 ± 2.0 nm, and the average particle size hardly changed even when the silver loading amount was changed. Also, the particle size distribution was relatively sharp. In contrast, for the samples prepared by the impregnation method or the photoelectrolysis method (Comparative Example 1 and Comparative Example 2), the average particle size was as large as 241 nm or 276 nm, and the particle size distribution was broad.
[0076]
Table 1
[0077] <Diffuse reflection spectrum> The diffuse reflection spectra obtained for Examples 1 to 4, Comparative Example 1, Comparative Example 2, and Comparative Example 4 are shown in FIG. 16. For the samples prepared by the ultrasonic reduction method (Examples 1 to 4), peaks were observed at wavelengths of 350 to 550 nm. Also, the peak intensity increased as the silver loading amount increased. In contrast, for the samples prepared by the impregnation method or the photoelectrodeposition method (Comparative Example 1 and Comparative Example 2) and the sample without silver loading (Comparative Example 4), no distinct peaks were observed at wavelengths of 350 to 550 nm. From this, it was found that the peaks observed at wavelengths of 350 nm to 550 nm were due to silver nanoparticles generated by ultrasonic reduction.
[0078] <CO2 reduction photocatalytic performance> The CO2 reduction photocatalytic performance (gas generation rate and CO selectivity) obtained for Examples 1 to 4, Comparative Example 1, Comparative Example 2, and Comparative Example 4 are shown in Table 2 and FIG. 17. The samples with silver nanoparticles supported by the ultrasonic reduction method (Examples 1 to 4) had a significantly higher CO selectivity than the sample without silver loading (Comparative Example 4). Also, the CO selectivity increased as the silver loading amount increased. It is presumed that charge separation was promoted by the loading of silver nanoparticles. In particular, for the sample with a loading amount of 0.5 mass% (Example 1), the CO gas generation rate was also maintained at a high level. On the other hand, the samples prepared by the impregnation method or the photoelectrodeposition method (Comparative Example 1 and Comparative Example 2) had inferior CO selectivity compared to the sample with the same loading amount prepared by the ultrasonic reduction method (Example 3).
[0079]
Table 2
[0080] [Experimental Example B] In Experimental Example B, the metal silver nanoparticle-supported gallium oxide particles obtained by reducing and generating silver nanoparticles by ultrasonic treatment were further heat-treated to prepare photocatalyst particles.
[0081] (1) Preparation of photocatalyst particles Example 7 The gallium oxide particles supported with silver metal nanoparticles obtained in Example 3 were heat-treated at 100 °C for 5 minutes in the atmosphere to prepare photocatalyst particles.
[0082] Example 8 The gallium oxide particles supported with silver metal nanoparticles obtained in Example 3 were heat-treated at 200 °C for 5 minutes in the atmosphere to prepare photocatalyst particles.
[0083] Example 9 The gallium oxide particles supported with silver metal nanoparticles obtained in Example 3 were heat-treated at 300 °C for 5 minutes in the atmosphere to prepare photocatalyst particles.
[0084] Example 10 The gallium oxide particles supported with silver metal nanoparticles obtained in Example 3 were heat-treated at 500 °C for 5 minutes in the atmosphere to prepare photocatalyst particles.
[0085] (2) Evaluation of photocatalyst particles For the obtained photocatalyst particles, evaluations of various properties were carried out as follows.
[0086] <SEM observation> SEM observation of the sample was carried out in the same manner as in Experimental Example A.
[0087] <TG-MS analysis> Thermogravimetry-mass (TG-MS) analysis of the sample was performed. The analysis was carried out using TG-DTA (Bruker-AXS, 2020SA / MS9600) at a heating rate of 10 °C / min in an N2-21% O2 atmosphere.
[0088] <X-ray diffraction (XRD)> The sample was analyzed using an X-ray diffractometer (Bruker, D8 DISCOVER Vario-1).
[0089] <CO2 reduction photocatalytic performance> The CO2 reduction photocatalytic performance of the sample was evaluated in the same manner as in Experimental Example A.
[0090] (3) Evaluation results <SEM image after heat treatment> SEM images of photocatalyst particles are shown in Figure 18. There was no significant change in the particle size of Ag nanoparticles in samples heat-treated at 200°C or less. On the other hand, in samples heat-treated at 300°C or more, there was an increase in particles with slightly smaller particle sizes.
[0091] <Changes in residual organic matter due to heat treatment> The TG curve and DTA curve of the photocatalyst particles are shown in Figures 19 and 20, respectively. In the sample before heat treatment (heating), CO2 was generated at around 180°C. This suggests that decomposition of organic matter occurs at this temperature. On the other hand, in the sample that was heat treated (heated) at temperatures above 200°C, no sudden CO2 generation was observed around 180°C. It is thought that the organic matter was decomposed by the heat treatment.
[0092] <Changes in Ag compounds due to heat treatment> The X-ray diffraction (XRD) pattern of the photocatalyst particles is shown in Figure 21. The generation of AgGaO2 was confirmed in samples heat-treated at temperatures above 200°C. As mentioned above, SEM observation showed that the particle size of the Ag nanoparticles was smaller in samples heat-treated at temperatures above 300°C. This is thought to be due to the conversion of some of the Ag nanoparticles to AgGaO2.
[0093] <Changes in catalytic activity due to heat treatment> The CO2 reduction photocatalytic performance (gas generation rate and CO selectivity) of the photocatalyst particles is shown in Table 3. It was confirmed that the CO selectivity was improved by heat treatment (heating).
[0094] [Table 3] [Explanation of symbols]
[0095] 2. Evaluation equipment 4 tanks 6 Mercury (Hg) Lamp 8 Gas introduction pipe 10 Gas exhaust pipe 12 pH meter 14 Rubber stopper 16. Stirrer 18 Bubbling Filter 20 Cooling water 22 Evaluation solution 30 CO2 gas 32 Gas evolution 34 Gas Chromatography
Claims
1. Gallium oxide (Ga 2 O 3 2.) Providing particles and a silver (Ag) source; adding the gallium oxide particles and the silver source to a reduction solution to prepare a reaction solution; and The reaction solution is irradiated with ultrasonic waves to produce gallium oxide particles carrying metallic silver nanoparticles; A method for producing carbon dioxide reducing photocatalyst particles, wherein, when the reaction solution is irradiated with ultrasonic waves, a surface portion of a silver source in the reaction solution is ultrasonically reduced to become metallic silver (Ag) nanoparticles, and the metallic silver (Ag) nanoparticles are supported on the surfaces of gallium oxide particles, The amount of the metallic silver nanoparticles supported is 0.3 to 10.0% by mass relative to the gallium oxide particles, and no organic protective agent is used.
2. The silver (Ag) source is silver oxide (Ag 2 The method of claim 1 , further comprising:
3. The method according to claim 1 or 2, wherein the reducing solution comprises an alcohol.
4. The method according to any one of claims 1 to 3, wherein the frequency of the ultrasound is 28 to 45 kHz.
5. The method according to any one of claims 1 to 4, wherein the ultrasonic irradiation is carried out for 1 to 10 hours.
6. The method according to any one of claims 1 to 5, wherein the gallium oxide particles carrying the metallic silver nanoparticles are subjected to a heat treatment at a temperature of 100 ° C. or higher in an oxygen-containing atmosphere.
7. The method according to any one of claims 1 to 6, wherein the metallic silver nanoparticles have an average particle size of 10.0 to 50.0 nm.
8. The method according to any one of claims 1 to 7, wherein the amount of metallic silver nanoparticles supported is 3.0 to 10.0% by mass relative to the gallium oxide particles.
9. CO 2 The method according to any one of claims 1 to 8, wherein the CO selectivity of the carbon dioxide reduction photocatalyst particles is 30% or more in a reduction photocatalyst performance evaluation test. However, the CO2 reduction photocatalyst performance evaluation test was performed under conditions in which an evaluation solution prepared by mixing ultrapure water (1 L), NaHCO3 (0.1 M) and the carbon dioxide reduction photocatalyst particles (0.5 g) was placed in a tank of an evaluation device, and then carbon dioxide (CO2) gas was blown in at a flow rate of 30 mL / min while UV light was irradiated from a 400 W high-pressure Hg lamp. The gas generated after one hour of irradiation was analyzed using gas chromatography to determine the H2, O2 and CO gas generation rates, and the CO selectivity was calculated based on the following formula (1). [0010]
10. CO 2 The method according to any one of claims 1 to 9, wherein the CO selectivity of the carbon dioxide reduction photocatalyst particles is 70% or more in a reduction photocatalyst performance evaluation test. However, the CO2 reduction photocatalyst performance evaluation test was performed under conditions in which an evaluation solution prepared by mixing ultrapure water (1 L), NaHCO3 (0.1 M) and the carbon dioxide reduction photocatalyst particles (0.5 g) was placed in a tank of an evaluation device, and then carbon dioxide (CO2) gas was blown in at a flow rate of 30 mL / min while UV light was irradiated from a 400 W high-pressure Hg lamp. The gas generated after one hour of irradiation was analyzed using gas chromatography to determine the H2, O2 and CO gas generation rates, and the CO selectivity was calculated based on the following formula (1). [0025]
11. The method according to any one of claims 1 to 10, wherein the photocatalyst particles have a peak in a wavelength range of 350 to 550 nm in a diffuse reflectance spectrum.
Citation Information
Patent Citations
BiOI (bismuth oxyiodide) / AgX (silver halide) visible light response photocatalyst, preparation methods for same and application thereof
CN102513135A
Method for manufacturing noble-metal nanomaterial
JP2008024968A
Metal nanoparticle and method for producing the composite powder
JP2010065265A
Method of reducing carbon dioxide
JP2012192302A